PWE-110 Gastro-oesophageal reflux in cystic fibrosis: exploring the impact on lung disease. (17th June 2017) - Lord, RW; Pearson, JS; Barry, PJ; Whorwell, PJ; Jones, RB; McNamara, PS; Beynon, R; Jones, AM; Smith, JA
Abstract : Introduction: Studies have shown large amounts of gastro-oesophageal reflux (GOR) in CF patients, which frequently has characteristics which may favour aspiration - asymptomatic, proximal oesophageal extent and supine. Exposure to refluxate may worsen CF lung disease, as it contains acid, digestive enzymes and microbes, which can include respiratory pathogens. We aim to establish if there is a relationship between GOR and CF lung disease. Method: We are conducting a prospective observational study in stable CF patients, measuring oesophageal reflux with combined pH and impedance (pH-MII) and reflux symptoms using the RESQ-7 questionnaire. In a preliminary analysis we have collected retrospective data from the medical records for lung function and number of courses of intravenous antibiotics. Results: 21 of 30 recruited completed the study (mean age 28 years, mean FEV1 50% predicted, 19 males). Total number of reflux episodes was increased in 72% (median 89, IQR 68–132, normal range <75 episodes). High risk reflux (increased proximal and/or supine reflux) was noted in 62%. Non-acid events (median 54, IQR 21–78) were more frequent than acid events (median 36.5, IQR 13–66), but 14/21 were on acid suppression medications. 5/21 had increased total reflux parameters (median 89, IQR 68–98), but on RESQ-7 had no symptoms. Interestingly, number of intravenous antibiotic treatments positively correlated with total reflux events (r=0.45, p=0.004) and suggested potential trends with high risk parameters (e.g. proximal reflux r=0.37, p=0.1). However there were no correlation between reflux parameters and spirometry. Conclusion: CF patients have large amounts of 'high-risk' reflux, and our data suggests a potential relationship between reflux severity and the number of pulmonary exacerbations, represented by the requirement for intravenous antibiotics. To explore this further a reliable biomarker of aspiration, such as sputum pepsin, is required. Disclosure of Interest: None Declared